The Power and the Responsibility: Implementation of the Wildlife and Hunting Provisions of the James Bay and Northern Quebec Agreement. - Feit, Harvey A. (Recherche amérindiennes au Québec, 1988)
In this “10 years after conference” presentation I examine the impacts of the James Bay and Northern Quebec Agreement (JBNQA – 1975) on the hunting activities of the Cree and Inuit peoples of the region from the point of view of their aspirations, and I look at the legal regimes and bureaucratic structures established from the point of view of their purposes in the Agreement. In the view of the majority of Cree people who supported the JBNQA, the provisions relating to hunting, fishing, and trapping were the most important and crucial features of the Agreement. Their aspirations, as I understood them from statements made In the Cree villages at the time, were twofold: (1) to provide for the continuation of their hunting societies - what has been called the hunting way of life - by reversing the governmental and development pressures which had been growing during the previous two decades, thereby enhancing the opportunities for the young and for future generations to continue hunting as a primary activity: and (2) to establish a new relationship with Quebec and Canada, a relationship of mutual respect and of mutual responsibility for the conservation of the resources themselves. In my view at the time the highly decentralized systems of isolated hunting camps and hunting territories that characterize Inuit and Cree hunting respectively meant that only the most general and therefore cumbersome government regulations could be enforced by a centralized authority. This situation provided an incentive for a common agreement that a regime involving both Aboriginal Peoples’ and governmental decisions could be in the interests of government wildlife management and of other wildlife users. Thus, there was a potential incentive to articulate the Indigenous systems with government management systems designed to achieve resource conservation and regulate non-native activities, and there could be a mutual benefit in doing so. Most of the specific provisions of the Agreement are designed around such needs. I consider how the JBNQA system has worked in its first 10 years practice. In particular. has it: a) provided new and effective management and protection of wildlife, and if not, why: and b) established a reciprocal respect between Aboriginal Peoples and government-mandated wildlife managers?
I am indebted to the many hunters of Waswanipi who have patiently tried to communicate some of their views and knowledge with me. I have benefited from the comments and advice of Lorraine Brooke, and those of Peter Hutchins, Paul Wilkinson, and Gaston Moisan who was the discussant for the conference paper. I have also drawn extensively on ideas and discussions held over several years with Cree administrators and with colleagues, many extensively involved in the implementation of the JBNQA, including: Philip Awashish, Fikret Berkes, Taylor Brelsford, Brian Craik, Thomas Coon, Rick Cuciurean, Billy Diamond, Jacob Gull, William Kemp, Abel Kitchen, Johnny Jolly, Ignatius LaRusic, James O'Reilly, Alan Penn, Richard Preston, Allan Saganash, Jr., Richard Salisbury, and Colin Scott.
Keywords: Wildlife Conservation; Decentralized Conservation Systems; Incentives for Co-governance; Aboriginal - Government Relations; James Bay and Northern Quebec Agreement (JBNQA); James Bay Cree; Northern Quebec Inuit